Los humedales altoandinos venezolanos: ¿lugares para la recreación y el turismo sustentable?. La visión de las comunidades locales del estado Táchira - Moncada, José Alí; Aranguren, Jesús (Tierra Infinita, 2015)
The HighAndean wetlands ecosystems are vital for the development of the Venezuelan Andes, due to the variety of benefits they provide to local communities. Within these values highlights its recreational, tourist and scenic value. The objective was to address the valuation, such as tourist space, which have high Andean wetlands of General Juan Pablo Peñalosa National Park on the Battalion and La Negra moors, for local communities associated with these ecosystems. It is a qualitative research approach conducted in Francisco de Miranda County, Tachira State. The information was collected through triangulation between: (1) Direct observation in the field by the research group, (2) The application of depth interviews with 18 key social actors involved in the use and conservation of lakes and (3) collection cultural products made by the community. The information collected was subjected to content analysis. Tourism activities are viewed from two perspectives: (1) as environmental risk and (2) as generating opportunities for local development. Finally, some proposals to develop sustainable tourism in the area are given.